Case Report: A case of acute kidney injury due to star fruit-infused liquor - Sichun Shan; Miao Shen; Jiajun Shi; Wei Liu (Frontiers in Medicine, 2026)
Oxalate nephropathy (ON) is a syndrome characterized by renal dysfunction accompanied by the deposition of calcium oxalate crystals within the renal tubules. We report a rare case of secondary ON in a patient who developed acute kidney injury (AKI) following the consumption of large quantities of star fruit-infused liquor. The patient’s clinical presentation was unremarkable; however, laboratory investigations revealed a rapid elevation in serum creatinine levels over a short period, meeting the clinical criteria for AKI. Initial diagnosis was challenging. After a thorough review of the medical history and kidney biopsy, a definitive diagnosis of secondary ON caused by oxalate deposition of star fruit origin was made. Following active treatment, the patient’s renal function gradually improved, but long-term follow-up indicated progression to chronic kidney disease (CKD). This report aims to underscore the importance of clinical recognition of secondary ON, emphasizing that early identification of its etiology is crucial for the prevention of subsequent renal injury.